Genetic Diversity of Acacia mangium Seed Orchard in Wonogiri Indonesia Using Microsatellite Markers - VIVI YUSKIANTI; KEIYA ISODA (Bogor Agricultural University, Indonesia, 2012)
Genetic diversity is important in tree improvement programs. To evaluate levels of genetic diversity of first generation Acacia mangium seedling seed orchard in Wonogiri, Central Java, Indonesia, three populations from each region of Papua New Guinea (PNG) and Queensland, Australia (QLD) were selected and analyzed using 25 microsatellite markers. Statistical analysis showed that PNG populations have higher number of detected alleles and level of genetic diversity than QLD populations. This study provides a basic information about the genetic background of the populations used in the development of an A. mangium seed orchard in Indonesia.